Warehouse Layout Reconfiguration Reduces Travel Distance Using Class Based Storage: Perubahan Tata Letak Gudang Mengurangi Jarak Perjalanan dengan Menggunakan Sistem Penyimpanan Berbasis Kategori - Vidiasari, Mike; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Warehouse layout plays a critical role in supporting material handling efficiency and operational performance in industrial systems. Specific Background: The studied company experienced excessive travel distance and disorganized item placement, leading to inefficiencies in retrieval and storage activities. Knowledge Gap: The existing warehouse arrangement had not applied a systematic storage classification based on item movement frequency, resulting in suboptimal space utilization and material flow. Aims: This study aims to redesign the warehouse layout using the Class Based Storage method to minimize travel distance and improve storage organization. Results: The analysis classified items into movement-based categories and proposed a new layout configuration that reduced total travel distance compared to the initial condition. The redesigned layout also improved accessibility for high-frequency items. Novelty: The study demonstrates the practical application of Class Based Storage in a specific industrial warehouse context supported by quantitative travel distance analysis. Implications: The findings provide a structured reference for warehouse management strategies focused on layout planning, storage classification, and operational efficiency improvement within industrial engineering practices. Keywords: Warehouse Layout, Class Based Storage, Travel Distance, Material Handling, Industrial Engineering Key Findings Highlights Storage classification based on movement frequency reorganized item placement systematically. Proposed configuration lowered total material transfer path compared to the initial arrangement. High-rotation products were positioned closer to access points to streamline retrieval activities.